1992
DOI: 10.1111/j.1469-8137.1992.tb00052.x
|View full text |Cite
|
Sign up to set email alerts
|

The physiological role of old stolon material in white clover (Trifolium repens L.)

Abstract: SUMMARYClonal plants of white clover {Trifolium repens L,), consisting of a single stolon plus roots and either three fully unfolded leaves or one fully unfolded leaf at the stolon apex, were grown in a controlled environment and sampled three times (after 7, 49 and 85 d growth) to examine the effects of increasing respiratory demand imposed by an increasing mass of old stolon material upon carbon allocation patterns and plant morphology.Where the total pool of available carbohydrate remained more-or-less cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…Up to now, only few studies have specifically investigated storage and re‐mobilization of resources in stolon internodes of clonal plants in an ecologic context. Tracer studies have shown that in Trifolium repens, a considerable part of the assimilated carbon is stored in stolon internodes (Chapman & Robson 1992 and references therein). Other authors have shown that storage of resources in stolon internodes of T. repens is also related to winter survival (Collins & Rhodes 1995; Turner & Pollock 1998), and that selection can act on the degree of stolon storage in this species (Collins et al 1997).…”
Section: Resource Storage In Clonal Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Up to now, only few studies have specifically investigated storage and re‐mobilization of resources in stolon internodes of clonal plants in an ecologic context. Tracer studies have shown that in Trifolium repens, a considerable part of the assimilated carbon is stored in stolon internodes (Chapman & Robson 1992 and references therein). Other authors have shown that storage of resources in stolon internodes of T. repens is also related to winter survival (Collins & Rhodes 1995; Turner & Pollock 1998), and that selection can act on the degree of stolon storage in this species (Collins et al 1997).…”
Section: Resource Storage In Clonal Plantsmentioning
confidence: 99%
“…In T. repens, stolon internodes usually contain a large percentage of biomass (Chapman & Robson 1992), and they are well protected against damage from grazers by their position close to the soil surface. The stolon system of T. repens seems thus functionally comparable to the extensive and long‐lived, belowground stem system of rhizomatous species.…”
Section: Resource Storage In Clonal Plantsmentioning
confidence: 99%
“…Restriction in forage supply during dry periods can also result in frequent grazing by livestock. Frequent defoliation has been reported to affect root growth (Jarvis & Macduff, 1989 ;Chapman & Robson, 1992 ;Singh & Sale, 1998). Restricted root growth in turn would probably affect water uptake from drying soil, and plant water status in terms of Ψ leaf and\or relative leaf water content, playing an important role in osmotic concentration, turgor pressure and cellwall extensibility.…”
Section: mentioning
confidence: 99%
“…Second, the large‐leaved type exhibits greater plasticity, by which it can persist under heavily grazed conditions for a lengthening period. Third, the large‐leaved type produces a larger amount of stolon, which also functions as a storage organ (Chapman & Robson 1992; Turner & Pollock 1998), promoting persistence under heavily grazed conditions for a period.…”
Section: Genetic Variation In Clonal Growth and Its Consequences For mentioning
confidence: 99%